Adoption Of Orcid And Other Persistent Identifiers In Kenya, Cote D'ivoire, Nigeria, And Across Africa – Opportunities And Lessons Learned - Tembo, Lombe; Havemann, Jo; Ezeike, Ebuka; Iyoha, Owen; Musangi, Peninnah; Coulibaly, Cecile (My University, 2023)
ORCID is the persistent identifier for researchers to share their accomplishments (research articles, data, etc with funding agencies, publishers, data repositories, and other research workflows. With this session, we aim to assist African researchers, librarians, and institutions in the adoption of digital tools and persistent identifiers for a significant increase of African research discoverability, globally and to increase efficiency in scholarly workflows
Keywords: African Research; Discoverability; Global Participation Program